Analisis Aktivitas Komunikasi Pemasaran Sooltanpay PT. Telkom Indonesia Di Platform Instagram - Aisy, Nafisa Rihadatul; Putri, Berlian Permadani Satria (eProceedings of Management, 2024)
The phenomenon of digital integrated payments is starting to be widely used by MSMEs in Indonesia. This is motivatedby the pattern of activities of the Indonesian people who are now increasingly adaptive to online shopping andtransacting activities. Of course, this phenomenon is well utilized by the organizers of digital payment applications,one of which is SooltanPay owned by PT. Telkom Indonesia Tbk. Even though it is relatively new, the existence ofSooltanPay as a digital payment provider application is starting to know a lot, especially on the Instagram platform,this is certainly inseparable from the broadcast marketing communication. Through this, this research aims toresearch marketing communication activities carried out by SooltanPay on Instagram social media. Research iscarried out with qualitative, descriptive methods with data collection through interview, observation, anddocumentation techniques and analyzed through Miles and Hubberman analysis techniques. The results of the studyfound that the marketing communication activities carried out by SooltanPay were appropriate even though it wasfound that the electronic word of mouth spread on this brand was negative. It is also related to the comments availableon SooltanPay's Instagram. Keywords-Integrated Marketing Communication, Digital Payment Applications, Instagram